Surgical Treatment Of Scar Microstomia - Madazimov Madaminzhon Muminovich; Teshaboev Muhammadyahyo Gulomkodirovich; Parpiev Abdumutal Lukmonzhonovich (Academia One, 2023)
This article reviews the results of surgical treatment of microstomia caused by scars around the mouth in 122 patients. When eliminating microstomia, the advantages of elimination using a double-humped flap formed by the internal mucous membrane of the oral cavity are mentioned. Using the above improved method of surgical treatment, it was possible to obtain good functional and aesthetic results in 96.9% of patients.
Keywords: surgical treatment; outcome; outcomeremoval of the internal mucous membrane of the oral cavity